1999
DOI: 10.1034/j.1399-0020.1999.282280212.x
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar ridge augmentation by distraction osteogenesis using titanium implants: an experimental study

Abstract: The left mandibular premolars were extracted from five adult dogs. After twelve weeks, a box-shaped osteotomy of the alveolar bone was carried out and two 10 mm implants were placed 5 mm into the transport alveolar segment, leaving 5 mm exposed. The alveolar bone was vertically augmented 5 mm by screwing the implants. After distraction, the implants were left to integrate into the bone. Histological and radiographical evaluations showed the lifting of the transport segment and the development of new bone in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 0 publications
1
24
0
2
Order By: Relevance
“…The resorption rates observed in this study are similar to those reported in studies where distraction osteosynthesis was performed. Augmentation using distraction osteogenesis have shown that 0.9-3.0 mm of resorption in the crestal bone height occurs (Block et al, 1996;Oda et al, 1999;Urbani et al, 1999;Jensen et al, 2002;Raghoebar et al, 2002). Distraction osteogenesis has several advantages: no need for bone harvesting; avoidance of donor site morbidity; vital bone in the distraction area; and gain of soft tissue.…”
Section: Discussionmentioning
confidence: 96%
“…The resorption rates observed in this study are similar to those reported in studies where distraction osteosynthesis was performed. Augmentation using distraction osteogenesis have shown that 0.9-3.0 mm of resorption in the crestal bone height occurs (Block et al, 1996;Oda et al, 1999;Urbani et al, 1999;Jensen et al, 2002;Raghoebar et al, 2002). Distraction osteogenesis has several advantages: no need for bone harvesting; avoidance of donor site morbidity; vital bone in the distraction area; and gain of soft tissue.…”
Section: Discussionmentioning
confidence: 96%
“…A thin alveolar ridge may result from bone resorption, as in the anterior maxillary region. In the alveolar ridge, experimental studies have demonstrated that distracted buccal bone tends to be thinner than distracted lingual bone, and both are thinner than non-distracted bone 4,51 . Changes in cortical thickness, with a tendency to produce an 'hourglass' appearance, are relatively common, and reflect the greater movement in the maxillofacial region 61 .…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Distraction osteogenesis has the potential to overcome these disadvantages, and in addition can provide lengthening of soft tissue together with new bone. [5][6][7] Various techniques of distraction osteogenesis have been described with reasonable success rates, and in recent years the idea of osteogenesis by periosteal distraction for the treatment of bone deficiencies has also been suggested. 1,2,8,9 The highly vascularised internal osteoblastic layer of periosteum plays a part in distraction osteogenesis.…”
Section: Introductionmentioning
confidence: 99%